O treinamento inspiratório com threshold aumenta a sensibilidade à insulina de pacientes idosos portadores de resistência à insulina - Silva, Mayra dos Santos [UNIFESP] (2010)
The physiological degenerations in the aging process can cause physiological decline in the pulmonary and metabolic function, being able to affect in the elder quality of life. The aging is association with insulin resistance, characterized for the reduction of the insulin reply to the stimulations, whose gradual effect can take the glucose intolerance and diabetes type 2. Therefore, the objective in this study was to investigate the influence of the inspiratory muscular training through the Threshold® on the insulin resistance in aged people. The study involved the participation of 14 elder voluntaries, with age between 61 and 82 years old, sedentaries, with BMI between 18,75 - 36,7 and insulin resistants with lipids alterations, of both genders, without previous pulmonary and cardiovascular disease at the clinic of the Taipas Hospital. The selected patients have been submitted to the Laboratorial Test, the physical Test and Cardiopulmonary Test. After the test, the patients were divided in two groups: Control group and Experimental Group. The program had duration of 12 weeks and both the groups did the inspiratory muscle training 07 times per week, being 06 times domiciliary and 01 time in the clinic with duration of 30 minutes daily. All tests were repeated after 12 weeks of inspiratory muscle training, where the comparison between the groups after the period of study showed that the group that suffered intervention got an improvement of the respiratory muscular performance and force, reduction of metabolic values. It being considered statistical significant the reduction of the values in glicemic, insulin and HOMA IR, this is important because the correlation between aging and insulin resistance. The data suggest that the inspiratory muscle training improves the insulin sensibility in insulin resistance patients.